Feasibility of Endoscopy-Assisted Laparoscopic Full-Thickness Resection for Superficial Duodenal Neoplasms. (16th January 2014) - Ohata, Ken; Murakami, Masahiko; Yamazaki, Kimiyasu; Nonaka, Kouichi; Misumi, Nobutsugu; Tashima, Tomoaki; Minato, Yohei; Shozushima, Meiko; Mitsui, Takahiro; Matsuhashi, Nobuyuki; Fu, Kuangi
Abstract : Background . Superficial duodenal neoplasms (SDNs) are a challenging target in the digestive tract. Surgical resection is invasive, and it is difficult to determine the site and extent of the lesion from outside the intestine and resect it locally. Endoscopic submucosal dissection (ESD) has scarcely been utilized in the treatment of duodenal tumors because of technical difficulties and possible delayed perforation due to the action of digestive juices. Thus, no standard treatments for SDNs have been established. To challenge this issue, we elaborated endoscopy-assisted laparoscopic full-thickness resection (EALFTR) and analyzed its feasibility and safety. Methods . Twenty-four SDNs in 22 consecutive patients treated by EALFTR between January 2011 and July 2012 were analyzed retrospectively. Results . All lesions were removed en bloc. The lateral and vertical margins of the specimens were negative for tumor cells in all cases. The mean sizes of the resected specimens and lesions were 28.9 mm (SD ± 10.5) and 13.3 mm (SD ± 11.6), respectively. The mean operation time and intraoperative estimated blood loss were 133 min (SD ± 45.2) and 16 ml (SD ± 21.1), respectively. Anastomotic leakage occurred in three patients (13.6%) postoperatively, but all were minor leakage and recovered conservatively. Anastomotic stenosis or bleeding did not occur. Conclusions . EALFTR can be a safe and minimally invasive treatment option for SDNs. However, the number of cases in this study was small, and further accumulations of cases and investigation are necessary.